6 - L’émergence et les perceptions des risques socio-environnementaux liés aux pratiques d’assainissement et aux usages de l’eau sur la lagune Aghien en Côte d’Ivoire. - Jonas, Ibo; Deroubaix José-Frédéric; Mitroi, Veronica; Kouadio, Chrislain Ahi (African Sociological Review, 2022)
The study of the socio-ecological risks in the villages bordering the Aghien Lagoon is based on the multiple water practices of the populations, whether these are direct practices (washing, bathing, swimming, defecation) or indirect practices (the management of household waste, excreta, waste water, farm waste). There is an important diversity of populations around the lagoon, both from a socio-cultural point of view and from a water and sanitation point of view. Our study considers the economic and technical constraints as well as historically rooted social relationships (social-cultural relationships with the lagoon) which lead to different sanitation practices and to various perceptions of environmental and health risks. At the junction of environmental and health conceptions of risk, we explain how environmental and human health are intimately linked in the risk’s perception by populations.